Implementasi Visual Studio pada Sistem Monitoring Daya dan Proteksi Rele Arus Lebih Menggunakan Automatic Transfer Switch/Automatic Main Failure (ATS/AMF) Disuplai oleh Kombinasi Grid dan Photovoltaic (PV) - Riftianto, Andrian Eko; Amirullah, Amirullah (Universitas Trunojoyo Madura, 2024)
Monitoring power consumption and protecting the use of household electrical equipment with separate and remote Internet of Things (IoT)-based energy sources, is an important requirement in modern times. This paper proposes the implementation of a voltage and current monitoring system resulting from the output of an automatic transfer switch/automatic main failure (ATS/AMF) supplied by a PLN (grid) source and a photovoltaic (PV) generator. This power electronics device is used to control the combination of two separate energy sources automatically. The PZEM-004t sensor functions to read the value of the output voltage and load current from the ATS/AMF. Arduino-Uno is used to control the protection relay so that it is able to disconnect or connect load currents where the parameters of current, voltage and power as well as the performance of the protection relay are all monitored by Visual-Studio. Test results on eight loads, namely: 30 W LED lamp, 15 W LED lamp, solder heater, cellular phone charger, laptop charger, 5 W spiral energy saving lamp (LHE), 5 W bulb lamp, and portable fan using the PZEM-004t sensor monitored by Visual Studio and validated by a multimeter, the average error values for voltage and current measurements were 0.448% and 14.561%, respectively. The results of the relay protection test show that if the source is connected to a load that absorbs the load current below 0.6 A, then the trip indicator on the overcurrent protection relay has not turned on so that the protection menu display in the Visual Studio application is OFF. On the other hand, if the total load current exceeds 0.6 A, the trip indicator on the protective relay will light up so that the switch will cut off the load current. In this condition, the display of the protection menu in the Visual Studio application is in ON status.